Emicizumab in the Treatment of Hemophilia A. Characteristics and clinical application - Bednarek, Ilona; Lach, Sylwia; Kowalczyk, Aleksandra; Pączek, Adrian; Dyczek, Paweł; Hofman, Julia; Staniszewska, Wiktoria; Jadanowski, Olaf; Błąd, Karol Seweryn (Journal of Education, Health and Sport, 2025)
Introduction: Hemophilia A is an inherited bleeding disorder caused by a congenital deficiency of factor VIII. It is characterized by a tendency for prolonged and excessive bleeding, both spontaneous and trauma-induced. The treatment of hemophilia A involves the use of factor VIII replacement therapy. In recent years, emicizumab-a modern, bispecific monoclonal antibody- has gained significant attention as an alternative to traditional treatment methods. Materials and methods : A total of 30 articles were analyzed, sourced from publicly available databases such as PubMed and Google Scholar. The selection focused on publications addressing molecular structure, pharmacokinetics, and treatment efficacy. The majority of the cited sources were published in English. State of knowledge: In this article, we will discuss the mechanism of action of emicizumab, its pharmacokinetics, and the benefits of its use in the treatment of hemophilia A, including a comparison with traditional therapies. The results of clinical trials will also be presented, confirming its efficacy, safety, and patient satisfaction, including in the context of treating patients with FVIII inhibitors.The goal is to present the effectiveness, safety, mechanism of action, and pharmacokinetic profile of emicizumab in bleeding prophylaxis for patients with hemophilia A. Conclusions: Emicizumab is a groundbreaking prophylactic treatment for hemophilia A, effective both in patients with and without factor VIII inhibitors, by mimicking the function of factor VIIIa. Clinical trials HAVEN 1–4 demonstrated the drug’s high efficacy in reducing bleeds and significantly lowering annual bleeding rates. Emicizumab has a favorable pharmacokinetic profile, allowing for infrequent dosing and improving therapy comfort compared to traditional treatment.